Enhancement Student Understanding Through The Development Of Lab Module Based On Constructivistic - Wiharyanto Oktiawan; Mochtar Hadiwodo; Purwono Purwono (Universitas Diponegoro, 2019)
Experimental focuses learning on developing the skills of student in the process of knowledge, discover and develop their own fact, concept, and values required. The way to make it is by doing modification to the practical guidance module had been given. Nowadays, practical guidance tend to emphasize on the explanation, so its use both practical and follow the path that has been presented. The practical guidance module should be modified based on constructivism. The module is an experimental guidance to environmental laboratory subject. The test material consists of water and wastewater sample with parameter of chemical oxygen demand (COD), total dissolved solid (TDS), and nitrate. The results showed progress in the cognitive aspects such students' ability to predict the concentration of COD sample. The greater COD concentration of wastewater make the color of mixture is blue-green. The student could communicate the calibration curves correctly. Hypothesis skills presented at TDS testing. The greater of the sediment, the greater the concentration of its. The same thing happened on COD testing, COD levels can be estimated earlier. The skills show an increasing such as the skill to ask questions, experiment planning skills, skills in using tools/materials, accuracy in data retrieval, seriousness and cooperation in conducting the experiment.